The Relationship between Training and Knowledge with Performance of Posyandu Cadres - Helmi Nurlaili; Nur Fitri Ayu Pertiwi (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2025)
One of the success of Posyandu servicesâ€™ indicators is cadres performance or activeness assessed by attendance during implementation and the amount of community participation coverage. Cadre performance is influenced by various factors, including knowledge about posyandu and training that has been attended. This study was to analyze the relationship between training and knowledge factors with the cadre's performance of Posyandu in Sidoagung Village, Kebumen Regency. This study was an analytic observation with a cross-sectional approach. The study sample was 33 posyandu cadres by accidental sampling. Data were collected through questionnaires and analyzed using the chi-square test. The 4 (66.7%) of 6 cadres who never had training had poor performance, and the 26 (96.3%) of 27 cadres who had training had good performance. There is a positive and significant relationship between training and cadres performance (Ï value <0.001). While 4 (50.0%) of 8 cadres with poor knowledge had poor performance, and 24 (96.0%) of 25 cadres with good knowledge had good performance. There is a positive and significant relationship between knowledge and cadres performance (Ï value 0.002). There is a positive and significant relationship between training and knowledge with the performance of posyandu cadres.